2022
DOI: 10.1007/s00520-022-06935-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy (TMA) in adult patients with solid tumors: a challenging complication in the era of emerging anticancer therapies

Abstract: Thrombotic microangiopathy (TMA) is a syndrome that encompasses a group of disorders defined by the presence of endothelial damage leading to abnormal activation of coagulation, microangiopathic hemolytic anemia and thrombocytopenia, occlusive (micro)vascular dysfunction, and organ damage. TMA may occur in patients with malignancy as a manifestation of cancer-related coagulopathy itself or tumor-induced TMA (Ti-TMA) as a paraneoplastic uncommon manifestation of Trousseau syndrome. TMA can also be triggered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Possible causes of thrombocytopenia in the present patient included cancer-therapy-related thrombocytopenia, exacerbation of MCTD, primary immune thrombocytopenia (ITP), and PTCP. Thrombocytopenia maybe caused by cancer directly with tumor involvement of bone marrow and spleen, which occurred most often in patients with known metastatic cancer and exacerbation of the disease ( 6 , 7 ). It was ruled out that the thrombocytopenia was directly caused by the ovarian cancer or cancer-associated factors with unremarkable biomarkers and MRI results.…”
Section: Discussionmentioning
confidence: 99%
“…Possible causes of thrombocytopenia in the present patient included cancer-therapy-related thrombocytopenia, exacerbation of MCTD, primary immune thrombocytopenia (ITP), and PTCP. Thrombocytopenia maybe caused by cancer directly with tumor involvement of bone marrow and spleen, which occurred most often in patients with known metastatic cancer and exacerbation of the disease ( 6 , 7 ). It was ruled out that the thrombocytopenia was directly caused by the ovarian cancer or cancer-associated factors with unremarkable biomarkers and MRI results.…”
Section: Discussionmentioning
confidence: 99%
“…As it is classically accepted that the development of secondary TMA results from the encounter of multiple triggers (“hits”) [6], it may be difficult to determine whether a drug can be considered causal, except in rare situations with strong chronological arguments (recurrence on rechallenge) or serological documentation of the pathogenic role of the drug. This is particularly the case for immune system targeting drugs/anticancer drugs, where the indication (i.e., solid cancer and autoimmune diseases) may be intrinsically associated with a risk of TMA [7], and in situations of co‐prescription of several potentially inducing drugs (e.g., calcineurin inhibitors with mammalian target of rapamycin inhibitors). For these drugs, the use of population‐based approaches may be particularly important to assess the potential association between drug exposure and TMA.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that 27% of patients with TMA were treated with drugs known to be able to trigger TMA development [6]. Drug‐associated TMA is becoming a real concern in the field of oncology [7]. Indeed, the worldwide development of new biotherapies has revolutionized many fields, including oncology, immunology, hematology, and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…TMAs are a group of disorders characterized by microangiopathic haemolytic anaemia and thrombocytopenia leading to microvascular occlusion and different levels of end-organ injury [ 21 ]. During the last few decades, the incidence of cancer drug-induced TMA has been reported to account for >15% of all TMAs, primarily due to the introduction of VEGF inhibitors [ 22 ].…”
Section: Discussionmentioning
confidence: 99%